GLOBAL INFLUENCES AND DOMESTIC DRIVERS: A HOLISTIC APPROACH TO RUPIAH EXCHANGE RATE DETERMINATION - Michelle Gravielle Benedicta Roring; Cevi Herdian (Jurnal Ekonomi dan Bisnis Airlangga, 2026)
Introduction: Fluctuations in the USD/IDR exchange rate significantly impact Indonesia’s macroeconomic stability. This study examines the short-term causal links between key macroeconomic variables and the USD/IDR exchange rate to identify the fundamental drivers of currency volatility. Methods: Using a quantitative approach, this research analyzes monthly time-series data from January 2014 to December 2024. Variables include interest rates, inflation, money supply, exports, imports, and global stock indices. The analytical framework employs stationarity testing, optimal lag selection, and Granger causality analysis within a Vector Autoregressive (VAR) model. Results: The findings reveal that imports are the only variable exerting a statistically significant short-run causal influence on the exchange rate. Increased imports elevate foreign currency demand, leading to Rupiah depreciation. Other factors, such as interest rates, inflation, money supply, exports, and global stocks, show no substantial predictive causation, suggesting their impacts are primarily reactive or structural. Conclusion and suggestion: USD/IDR movements are predominantly driven by real-sector trade pressures, specifically import reliance. To strengthen the Rupiah, policies should prioritize managing import growth and boosting domestic productive capacity, with monetary strategies serving a supplementary role in maintaining stability.